Glacial style and ice limits, the Quaternary stratigraphic record, and changes of land and ocean level in the Atlantic Provinces, Canada - Grant, D. (Géographie physique et Quaternaire, 1977)
Evidence from scattered stratigraphie sections, from the relationship of a sequence of ice flow indicators to a raised interglacial marine platform, together with the limits of freshly glaciated terrain against weathered bedrock areas, indicates that late Wisconsinan glaciers spread weakly toward, and in many areas not beyond, the present coast. These were fed by a complex of small ice caps located on broad lowlands and uplands. The limiting factor was the deep submarine channels that transect the region. Thus, Laurentide ice was limited to northern Gulf of St. Lawrence. With this pattern of centripetal flow toward the Gulf, large areas remained unglacierized. There is now better geological corroboration of Fer-nald's hypothesis of nunatak botanic réfugia, though there was, perhaps during early Wisconsinan time, grounded ice in the Gulf and an outlet glacier in Laurentian Channel. Raised postglacial shorelines fit the model, with a general tilt toward the main shield ice sheet, but with two broad domes reflecting the ice complexes over New Brunswick and Newfoundland. Older emerged and submerged shorelines beyond the glacial limit complicate the pattern. At present northern regions are still rebounding while a zone of subsidence is migrating inland from the continental margin.